دور الحواظر الثقافية في المغرب الاسلامي وافريقيا جنوب الصحراء – مظاهر التأثير و التأثر - وصال حمدي; منى لبشاقي (My University, 2023)
Summary: This study aims to reveal the role of cultural cities in the Islamic Maghreb and in sub-Saharan Africa, while highlighting the manifestations of influence and vulnerability, by addressing that these cities have played a civilized role in the process of intellectual and cultural construction, and this importance has given them an exceptional status because they contain various scientific and cultural institutions such as schools and mosques and libraries, which have made them a center of scientific and intellectual radiation, as several means of communication have contributed between the Maghreb Islam and Africa south of the Sahara, such as the commercial caravans and the movement of scholars, which led to the spread of the Arabic language and Islamic doctrines in Africa, in addition to the scientific voyages which were at the origin of the consolidation of cultural relations. ----------------------------- الملخص : تهدف هذه الدراسة للكشف عن دور الحواضر الثقافية في المغرب الإسلامي وإفريقيا جنوب الصحراء ، مع إبراز مظاهر التأثير والتأثر ، وذلك من خلال التطرق إلى أن هذه الحواضر لعبت دور حضاري في عملية البناء الفكري والثقافي وهذه الاهمية جعلتهم يحضون بمنزلة إستثنائية لإحتوائهم لمختلف المؤسسات العلمية والثقافية من مدارس و مساجد ومكتبات ، وهو ما جعلهم مركزا للإشعاع العلمي و الفكري حيث ساهمت عدة وسائل للتواصل بين المغرب الإسلامي وإفريقيا جنوب الصحراء كالقوافل التجارية وتنقل العلماء ، مما أدى إلى إنتشار اللغة العربية والمذاهب الإسلامية بإفريقيا إضافة إلى الرحلات العلمية التي كانت سبب في توطيد العلاقات الثقافية . --------------------------------- Résumé : Cette étude vise à révéler le rôle des villes culturelles au Maghreb islamique et en Afrique subsaharienne, tout en soulignant les manifestations d'influence et de vulnérabilité, en abordant que ces villes ont joué un rôle civilisé dans le processus de construction intellectuelle et culturelle, et cette importance leur a conféré un statut exceptionnel car ils contiennent diverses institutions scientifiques et culturelles telles que des écoles et des mosquées et des bibliothèques, ce qui en a fait un centre de rayonnement scientifique et intellectuel, comme plusieurs moyens de communication ont contribué entre le Maghreb islamique et l'Afrique au sud du Sahara, comme les caravanes commerciales et le mouvement des savants, qui ont conduit à la diffusion de la langue arabe et des doctrines islamiques en Afrique, en plus des voyages scientifiques qui ont été à l'origine de la consolidation des relations culturelles.